La lectura crítica y su influencia en el rendimiento académico de los estudiantes del sexto año de educación básica de la escuela federación deportiva de Cotopaxi de la parroquia El Carmen cantón La Maná durante el periodo 2012 –2013 - Ayala Alvarrasín, Héctor Ricardo (2014)
Critical reading is a problem that has caused many problems in education many of them presented by the poor training received by teachers who do not know the influence of inadequate reading in the academic performance of students from “Federación Deportiva de Cotopaxi” school, for this reason it was taken the initiative to carry out this research work that aims to determine the influence of critical reading in the sixth year students of Basic Education, to establish the influence that it has on school performance and design a training proposal to the educational community, for this survey was applied to teachers, parents and students where it was observed that from a population of 39 students, 15 students managed a good reading level.